Cooperation between the European Union and European Mini-States – Possible Scenarios for Future Closer and Enhanced Integration with the European Union - Kalicka-Mikołajczyk, Adriana (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Within Europe, there are a number of small, independent and internationally recognised states which are the European Union’s neighbours; however they are not members of this organisation: the Principality of Andorra, the Republic of San Marino, the Principality of Monaco. In December 2010, the Council concluded that EU relations with these three Mini-States were “extensive but fragmented”, as there are still obstacles to introduce free movement of persons, goods and services into and out of the EU. Citizens and companies of all three Mini-States have limited access to the EU’s internal market. The most problematic areas are the free movement of persons and services, and the freedom of establishment. Goods originating in these States also encounter obstacles regarding the free movement of goods in so far as EU standards and regulations may prevent these goods from being sold within the EU market. EU citizens and businesses would also benefit from greater integration with Mini-States. EU citizens currently require a permit to work and/or reside in each of the Mini-States. However, all of the Mini-States have expressed the wish to enhance their relations with the EU, notwithstanding there being some differences of emphasis in terms of extent and scope. Andorra has expressed an openness to consider various options short of EU accession, while voicing a certain preference for an Association Agreement. Monaco has also expressed an interest to further discuss options for its closer integration into the internal market. Finally, San Marino has expressed an openness to consider a wide range of options for enhanced European integration, ranging from EEA Membership to a multilateral or bilateral Association Agreement with the EU. All three countries wish to safeguard their specificities and identities in their relations with the EU. The main objective of this paper is to examine the possibilities of future deeper and enhanced cooperation between the EU and these three Mini-States.
Keywords: minipaństwa; Księstwo Andory; Republika San Marino; Księstwo Monako; Unia Europejska; współpraca